2012
DOI: 10.1155/2012/264609
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release Kinetics from Polymer Matrix through Fractal Approximation of Motion

Abstract: The present paper analyzes the process of drug release from polymer matrix. This process has been considered as fractal polymer process. Since complexity of physical processes is replaced by fractality, the paper studies the process through fractal approach. In drug dynamics, fractal "diffusion" equation can be obtained through fractal approximation of motion. All experimental release curves have been best demonstrated by Weibull relation (which was, in its turn, also demonstrated). Weibull parameters are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This indicates increased complexity and tortuosity of tolfenamic acid and bupivacaine clusters in the UHMWPE matrix. Previously we demonstrated that the initial release is primarily driven by the “small” drug clusters, 16 and increased fractal dimension is often associated with increased drug diffusion from the polymeric matrix 44,45 . We attribute the pronounced increase in the tolfenamic elution to the increased complexity and tortuosity of “small” drug clusters.…”
Section: Discussionmentioning
confidence: 72%
“…This indicates increased complexity and tortuosity of tolfenamic acid and bupivacaine clusters in the UHMWPE matrix. Previously we demonstrated that the initial release is primarily driven by the “small” drug clusters, 16 and increased fractal dimension is often associated with increased drug diffusion from the polymeric matrix 44,45 . We attribute the pronounced increase in the tolfenamic elution to the increased complexity and tortuosity of “small” drug clusters.…”
Section: Discussionmentioning
confidence: 72%